PHENOMENON REFRACTION AND SHOALING OF WAVES ON BEACH - MAGDALENA (NIM : 20110009), IKHA
Wave shoaling and refraction are two phenomena that occur as a train of waves propagates into shallow water area. Shoaling is a phenomenon of increasing wave amplitude when the wave approach the beach. Portions of a wave located in deeper water travel faster than those in shallower water, so that the wave pattern experiences a gradual change of its orientation, which is called wave refraction. In this thesis we use the Shallow Water Equations (SWE) to study those two phenomena. The shallow water equations consists of mass conservation and momentum balance, expressed in variables surface elevation and horizontal velocity of fluid particle. Numerical simulation of SWE clearly show wave shoaling and refraction phenomena as waves approaches the shore. Numerical methods used is the finite volume method on a staggered grid. This method is conditionally stable and non-dissipative. From energy conservation principle we obtain formulas for wave refraction and shoaling coefficients analytically. For the case of straight and parallel bottom contour, both coeffcients can be determined directly. Wave refraction and shoaling coeffcients from numerical results show good agreement with the analytical results. We simulate wave focusing due to an artificial sill on a sloping bottom. It can explain that the topography bathymetry affect the behavior of the wave above.